Dose-resposta e tempo-resposta da fotobiomodulação de corpo inteiro sobre a glicemia de homens com diabetes mellitus tipo II: ensaio clínico randomizado, duplo-cego e sham-controlado - Rocha, Francisco Costa da (Universidade Federal de São Carlos, 2026)
This dissertation investigated the effects of whole-body photobiomodulation (PBM) using infrared light on glycemic control in men with type 2 diabetes mellitus (T2DM). T2DM is one of the most prevalent chronic diseases worldwide and is characterized by persistent hyperglycemia associated with insulin resistance, systemic inflammation, oxidative stress, and mitochondrial dysfunction. Conventional treatment is primarily based on the use ofhypoglycemic medications combined with lifestyle modifications. However, therapeutic adherence is often limited, which has stimulated the search for complementary nopharmacological interventions. In this context, photobiomodulation has been proposed as a promising strategy for metabolic modulation and improvement of glycemic control. The dissertation was structured into two main studies. The first consisted of a systematic review of the literature aimed at synthesizing the available evidence regarding the effects of photobiomodulation on glycemic control in individuals with T2DM. Overall, the results demonstrated significant reductions in fasting blood glucose and glycated hemoglobin, in addition to improvements in metabolic and hemodynamic parameters. However, the review also highlighted important limitations, including the small number of available studies, heterogeneity in the application protocols, and a moderate risk of bias, indicating the need formore robust clinical trials. The second study consisted of a randomized, double-blind, shamcontrolled clinical trial designed to investigate the dose-response and time-response effects of whole-body photobiomodulation on blood glucose levels in men with T2DM. A total of 40 volunteers participated in the study, with a mean age of approximately 60 years, and were randomly allocated into four groups: PBM for 10 minutes, 20 minutes, 30 minutes, or a sham intervention. The therapy was delivered using an infrared LED panel (850 nm) that irradiated the participants’ entire body. Capillary blood glucose was monitored at multiple time points: preprandial, postprandial, and at 1, 3, 6, 12, and 24 hours after the therapy session. The results showed that photobiomodulation promoted significantly greater reductions in blood glucose compared to the sham group, particularly during the first hours following the intervention. The most pronounced reductions were observed at 1 and 3 hours after treatment, with partial maintenance of the effect up to 12 hours. In contrast, no statistically significant differences between groups were observed at the 6- and 24-hour time points. The area-under-the-curve analysis indicated that the 10-minute and 30-minute protocols produced the greatest overall reductions in blood glucose levels, suggesting a non-linear response in relation to light exposure time. In conclusion, whole-body photobiomodulation using infrared LED light may promote acute reductions in plasma glucose during the postprandial period in men with T2DM, with effects that may persist for up to 12 hours after a single session without the use of hypoglycemic medications. These findings suggest that PBM may represent a promising adjunct therapeutic strategy for metabolic control in T2DM, contributing to scientific advancement and to the development of new non-pharmacological approaches for disease management. Nevertheless, additional studies are required to confirm these findings and to establish optimal clinical parameters for its application.
Dose–response and time–response effects of whole-body photobiomodulation on blood glucose in men with type 2 diabetes mellitus: a randomized, double-blind, sham-controlled clinical trial
Keywords: Fotobiomodulação; Diabetes mellitus tipo 2; Controle glicêmico; Luz infravermelho; Ensaio clínico randomizado; Photobiomodulation; Type 2 diabetes mellitus; Glycemic control; Infrared light; Randomized clinical trial; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar